Impact of Audit and Financial Factors on Audit Report Lag: Evidences from Indonesian - Andy Dwi Bayu Bawono; Noer Sasongko; Mustofa Mustofa (Riset Akuntansi dan Keuangan Indonesia, 2023)
Financial report relevance, which is one of the qualitative features of financial reports, can be affected by audit report lag. Less pertinent is the audited financial report of a local government the longer the audit report is delayed. Thus, the user of a local government financial report may experience negative consequences. This study’s objective was to examine empirical evidence about the influence of audit results, auditor switches, local government size, leverage, and profitability on local government audit report lag in Indonesia. This study utilized 506 out of 514 local governments (districts and cities) in Indonesia during 2017 and 2018, with a total sample size of 1,012. This study utilized secondary data collected from 2017 to 2018 audit reports of the Supreme Audit Institute – SAI (BPK). The data was collected from the electronic database services of the Information and Documentation Executive Authority (E-PPID) at http://e-ppid.bpk.go.id. The Purposive Sampling Technique was used to acquire the sample, and the data was analyzed using Ordinary Least Squares (OLS). According to the research, audit findings, local government size, and leverage influenced local government audit report latency, but auditor changes and profitability had no significant effect. Many variables, including audit opinion, audit quality, auditor experience, the quantity of capital expenditures, special allocation funds received by local government, and the qualifications of the local government report compiler, might be investigated further. In addition, splitting municipal governments depending on island location would provide for an intriguing extra audit report lag study.